2022
DOI: 10.2172/1871912
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Process Intensification: Transforming the Way Industry Uses Thermal Process Energy (Workshop Report)

Abstract: 2012. Reducing CO2 emissions from heavy industry: A review of technologies and considerations for policy makers. Retrieved from https://www.imperial.ac.uk/media/imperialcollege/grantham-institute/public/publications/briefing-papers/Reducing-CO2-emissions-from-heavy-industry---Grantham-BP-7.pdf. 10 DOE (US Department of Energy). 2018. Manufacturing Energy and Carbon Footprints (2014 MECS). Retrieved from https://www.energy.gov/eere/amo/manufacturing-energy-and-carbon-footprints-2014-mecs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Studies have identified various decarbonization pillars as viable options for industries to reduce emissions [5,6]. The U.S. Department of Energy's (DOE's) Industrial Decarbonization Roadmap identified four pillars: energy efficiency; industrial electrification; low-carbon fuels, feedstocks, and energy sources (LCFFES); and carbon capture, utilization, and storage (CCUS), as shown in Figure 3 [7]. The energy efficiency pillar focuses on lowering energy demand, and therefore the CO 2 emissions from fossil fuel combustion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have identified various decarbonization pillars as viable options for industries to reduce emissions [5,6]. The U.S. Department of Energy's (DOE's) Industrial Decarbonization Roadmap identified four pillars: energy efficiency; industrial electrification; low-carbon fuels, feedstocks, and energy sources (LCFFES); and carbon capture, utilization, and storage (CCUS), as shown in Figure 3 [7]. The energy efficiency pillar focuses on lowering energy demand, and therefore the CO 2 emissions from fossil fuel combustion.…”
Section: Introductionmentioning
confidence: 99%
“…The final pillar, CCUS, is aimed at capturing the difficult-to-abate CO 2 emissions at the source or directly from the atmosphere. The captured CO 2 emissions can either be utilized or stored for longer periods to prevent it entering the atmosphere [7]. both grid and on-site electricity generation sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glass has a high energy intensity due to the temperatures required to form the glass melt and generate products with uniform properties. The stages for glass production follow the same order of operation despite having differing material specifications, beginning with batch formation of raw materials, followed by melting and homogenization of batch materials, refining, forming, and post-processing (Cresko et al 2022). Despite the high energy intensity, energy demand for glass production was only 0.8% of the U.S. total energy demand for 2018, as glass has lower production volumes than other commodities such as cement, metals, or pulp and paper (U.S. EIA 2018).…”
Section: Introductionmentioning
confidence: 99%